2013
DOI: 10.1016/j.cmet.2012.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Sensor O-GlcNAcylation Coordinates with Phosphorylation to Regulate Circadian Clock

Abstract: SUMMARY Post-translational modifications play central roles in myriad biological pathways including circadian regulation. We employed a circadian proteomic approach to demonstrate that circadian timing of phosphorylation is a critical factor in regulating complex GSK3β dependent pathways and identified O-GlcNAc transferase (OGT) as a substrate of GSK3β. Interestingly, OGT activity is regulated by GSK3β, hence OGT and GSK3β exhibit reciprocal regulation. Modulating OGlcNAcylation levels alter circadian period l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
215
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(241 citation statements)
references
References 52 publications
(64 reference statements)
11
215
1
1
Order By: Relevance
“…In mammals, O-GlcNAc modification has been implicated in circadian clock function through regulating circadian clock genes, including PERIOD (49), BMAL1 (50), and CLOCK (51,52). Although these clock components are not conserved in plants, we found O-GlcNAc modification of proteins involved in plant circadian clock function, including TIME FOR COFFEE (TIC) (53).…”
Section: Potential Roles Of O-glcnacylation In the Circadian Clock Fmentioning
confidence: 74%
“…In mammals, O-GlcNAc modification has been implicated in circadian clock function through regulating circadian clock genes, including PERIOD (49), BMAL1 (50), and CLOCK (51,52). Although these clock components are not conserved in plants, we found O-GlcNAc modification of proteins involved in plant circadian clock function, including TIME FOR COFFEE (TIC) (53).…”
Section: Potential Roles Of O-glcnacylation In the Circadian Clock Fmentioning
confidence: 74%
“…In some cases, O-GlcNAc modifications and phosphorylation compete for the same target serines or threonines 9,10 . Such competition targeting the same substrate has recently been demonstrated in circadian-clock regulation 11 . Thus, there are multiple layers of regulation in complicated biological networks of protein regulation 10 .…”
Section: Instructions For Reviewing Your Article Proofmentioning
confidence: 99%
“…We have previously found that O-GlcNAcylation in the FASP serine cluster (amino acids 662-674) of PER2 competes with phosphorylation at the same sites 11 . O-GlcNAcylation catalyzed by O-GlcNAc transferase (OGT) increases the repressor activity of PER2 and decreases protein stability (Fig.…”
Section: Multiple Modifications Antagonizing Per Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Un autre facteur impliqué dans le dialogue entre horloge et métabolisme est la réaction de O-glycosylation qui est directement proportionnelle à la quantité de UDP-GlcNAc provenant du métabolisme du glucose, des acides gras et des acides aminés. Plusieurs études ont montré que la O-glycosylation interfère avec la phosphorylation et l'ubiquitination, et donc intervient dans la stabilité et l'activité des protéines CLOCK, Per, et Cry, aboutissant à une augmentation de la période du cycle, et à une altération de l'homéostasie glucidique [29,30]. Enfin, le statut d'oxydoréduction de la cellule influence le fonctionnement de l'horloge au travers du rapport NAD(P) + /NAD(P)H, dont l'augmentation se traduit par une diminution de l'interaction de CLOCK/BMAL1 avec l'ADN [31].…”
Section: Les Acteurs Du Couplage Horloge-métabolismeunclassified